On the abundance and occurrence of the mangrove crabs, Scylla spp. (Crustacea: Portunidae) from Munjang mangrove, Bangka Belitung Island - Raniah, Nadhifah; Henri, Henri; Kurniawan, Kurniawan (Jurnal Riset Biologi dan Aplikasinya, 2022)
The mangrove ecosystem is one of the most productive ecosystems on earth. This ecosystem provides a lot of functions for the living organism inhabiting here, such as fishes, mollusks, echinoderms, crustaceans, ect. The mangrove crab is one of the common crustaceans that can be found in the mangrove. This Purtunidae crab is very popular due to their role in the food chain as well as for the economic income that has a high value in the market. However, overexploitation may decrease the crab population. This study aimed to investigate the abundance and occurrence of the mangrove crabs from Munjang mangrove, Bangka Belitung Island from August 2020 to June 2021 using baited traps with the line transect method at four zones. A total of four species of mangrove crabs, Scylla olivacea, S. paramamosain, S. serrata and S. tranquebarica, were found in this location and dominated by S. serrata. Shannon diversity index (H’) was a in low category (<1), evenness index range (J) from 0.35 to 0.89, and there was dominant species in this study. The bed sediment iswas dominated by the muddy clay substratum except in zone 4 with sandy. Overall, this location is a suitable habitat for the Scylla spp. And better management is urgently needed before these crabs are exploited by humans.